Ultrazvočna diagnostika akutnega vnetja slepiča ter njen vpliv na kirurško odločitev - Vidmar, Dubravka (Endoskopska revija, 2009)
Background. For about one hundred years, the clinical diagnosis of acute appendicitis was based on case history and physical examination, which resulted in a high rate of negative laparotomies. The rate began to decreases ignificantly after the introduction of preoperative diagnostic imaging. Ultrasound (US) has proved to be an ideal diagnostic imaging procedure. There is still considerable debate over whether to use it routinely in all patients or to employ it only in individuals with ambiguous clinical findings. Aim. To evaluate the efficacy of ultrasound in reducing the rate of negative laparotomies, as well as to determine the value of probes with different frequency ranges and appraise the impact of the examiner's experience on the outcome of examination. Patients and methods. US examinations were performed consecutively and prospectively in 300 adult patients with suspected acute appendicitis. The sensitivity, specificity, accuracy, positive and negative predictive value of ultrasonography, and the rate of negative laparotomies were calculated. The outcome was correlated with the examiner's experience, and the efficacy of different probes was evaluated. Results. The sensitivity was 91.0 %, specificity 95.9 %, negative predictive value 90.8 %, positive predictive value 95.9 %, and accuracy 93.3 %. The negative laparotomy rate was4.8 %. The examiner's experience had a significant impact on the examination outcome. In 23.8 % of cases, the inflammed appendix could not be visualized with the high-frequency linear probe. Both probes were equally effective in 9.5 % of patients. Conclusion. US is a highly accurate diagnostictool for the evaluation of acute appendicitis when performed by an experienced sonologist, using probes with a wide frequency range. With a routine use of US a very low rate of negative laparotomies may be achieved
Keywords: Appendicitis; Občutljivost in specifičnost; Diagnosis; Laparotomija; slepo črevo; Ultrasonography; vnetja; Surgery; Laparotomy; ultrazvočna diagnostika; kirurško zdravljenje; Sensitivity And Specificity; Apendicitis